2018
DOI: 10.15694/mep.2018.0000103.1
|View full text |Cite
|
Sign up to set email alerts
|

Hand-held ultrasonography: An opportunity for “hands-on” teaching of medicine

Abstract: Background: As ultrasound offers students an opportunity to study anatomy, physiology and pathophysiology actively, we used hand-held ultrasound (HHU) devices to augment current teaching of cardiac murmurs and pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…General Electric's Vscan was exclusively used in 11 studies [31][32][33][34][35][36][37][38][39]41,43,49,51,53,54]. Two studies used the Acuson P10 (Siemens, [29,54]), two used the Philips Lumify [50,52], three used the Butterfly iQ [44,45,47], and one used the Ballater Medical 3-in-1 ultrasound probe (Ballater Medical, Edinburgh, UK) [46].…”
Section: The Handheld Ultrasound Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…General Electric's Vscan was exclusively used in 11 studies [31][32][33][34][35][36][37][38][39]41,43,49,51,53,54]. Two studies used the Acuson P10 (Siemens, [29,54]), two used the Philips Lumify [50,52], three used the Butterfly iQ [44,45,47], and one used the Ballater Medical 3-in-1 ultrasound probe (Ballater Medical, Edinburgh, UK) [46].…”
Section: The Handheld Ultrasound Devicesmentioning
confidence: 99%
“…It has already been demonstrated that short-term (a few hours to a few days) handheld ultrasound training can significantly improve students' and residents' abilities to capture and interpret specific ultrasound images accurately [31,[33][34][35]41,42,44]. Limiting the number of trainees in a group and increasing the number of procedures per trainee improve performance [38]. Short-duration courses might increase the number of false positive diagnoses, highlighting the importance of sufficient practice [48].…”
Section: Rethinking Medical Educationmentioning
confidence: 99%